Peningkatan Kemampuan Menulis Karangan Narasi dengan Menggunakan Model Pembelajaran Brain Based Learning Siswa Kelas VI SD Negeri pada Kecamatan Wangi-Wangi Kabupaten Wakatobi - Shia Anissa Dwinasari; Aliem Bahri; Anin Asnidar (Journal on Education, 2024)
The purpose of this research is to determine "Improving the Ability to Write Narrative Essays of Grade VI Students of Pada Pada State Elementary Schools Through the Application of the Brain Based Learning Model". The type of research used in this research is Classroom Action Research (PTK) which is carried out collaboratively between researchers and sixth grade teacher. The subjects in this research were 10 class VI students, with details of 3 boys and 7 girls. The data collection techniques in this research were tests of students' narrative essay writing abilities, observation and documentation. The data analysis technique uses quantitative analysis techniques and finds the average. The indicator of the success of this research is that if individual students get a KKM score of 70, then classically 80% of students achieve the KKM score out of all class VI students. The research results show that the ability to write narrative essays can be improved by using the Brain Based Learning learning model. This increase can be seen from the test results for each meeting carried out by researchers in cycle I. Meeting I was 53%, while at meeting II it increased to 62% and the test results in cycle II, meeting I obtained a score of 75% and at meeting II increased to 84%.